2012
DOI: 10.1093/jrr/rrs104
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of light scattering intensities of the crystalline lens for radiation related minimal change in interventional radiologists: a cross-sectional pilot study

Abstract: To evaluate low-dose X-ray radiation effects on the eye by measuring the amount of light scattering in specific regions of the lens, we compared exposed subjects (interventional radiologists) with unexposed subjects (employees of medical service companies), as a pilot study. According to numerous exclusionary rules, subjects with confounding variables contributing to cataract formation were excluded. Left eye examinations were performed on 68 exposed subjects and 171 unexposed subjects. The eye examinations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Compared to slit lamp retroillumination, the Scheimpflug system allows objective quantification of posterior capsule opacification much easier because the images are free of flash reflections (Jain and Grewal 2009 ). Using the Scheimpflug technique, Jeon and Kim ( 2011 ) observed 26% posterior-subcapsular cataracts among highly myopic patients who underwent cataract surgery, and Abe et al ( 2013 ) reported also posterior-subcapsular opacities after radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to slit lamp retroillumination, the Scheimpflug system allows objective quantification of posterior capsule opacification much easier because the images are free of flash reflections (Jain and Grewal 2009 ). Using the Scheimpflug technique, Jeon and Kim ( 2011 ) observed 26% posterior-subcapsular cataracts among highly myopic patients who underwent cataract surgery, and Abe et al ( 2013 ) reported also posterior-subcapsular opacities after radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,12,14 The intensive use of fluoroscopy among unprotected interventional cardiologists and nurses, compared with a matched control group, has been associated with statistically significant dose-dependent increased risk of posterior lens opacities. 2,7,9,14 Moreover, a 20-year prospective cohort study, among over 35 000 radiological technologists, has reported that exposure to fluoroscopic radiation doses, lower than recommended by the International Commission on Radiological Protection (ICRP), may increase the long-term risk of cataract formation. 6 Similar studies have proposed a correlation linking excessive radiation to the eye lens with the increased prevalence of early onset cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization has recognized cataract as the most prevalent eye disease in the world, and the association of excessive eye radiation exposure and the premature development of cataracts has been previously reported. 2,7,12,14,21 The current concept on the pathogenesis of radiation-induced cataract formation suggests that oxidative stress generated by elevated radiation levels results in the generation of reactive oxygen species and increased DNA damage at the lens epithelium. Such cumulative eye damage may result in cataracts and diminished visual acuity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, skin erythema is associated with an exposure threshold of approximately 2 Gy and permanent skin injury with an exposure threshold of about 5 Gy 4 5. For operators, the eye lens is susceptible and cataract risk increases with acute exposure as low as 0.1 Gy and chronic exposure of 5 Gy 6. The potential long-term effects to patients from repetitive exposure to ionizing radiation during medical procedures, however, are less well understood,7 and the cumulative stochastic effects on operators and support personnel from chronic low-level radiation exposure remain unclear 8 9.…”
Section: Introductionmentioning
confidence: 99%